2001
DOI: 10.1037/0278-7393.27.1.294
|View full text |Cite
|
Sign up to set email alerts
|

Representational momentum and Michotte's "launching effect" paradigm (1946/1963).

Abstract: In A. Michotte's (1946/1963) launching effect, a moving launcher contacts a stationary target, and then the launcher becomes stationary and the target begins to move. In this experiment, observers viewed modifications of a launching effect display, and displacement in memory for the location of targets was measured. Forward displacement of targets in launching effect displays was decreased relative to that of targets (a) that were presented in isolation and either moved at a constant fast or slow velocity or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 24 publications
4
68
0
1
Order By: Relevance
“…Perhaps the most studied of these factors that affect judgements of causality is temporal contiguity. Michotte ([47], and see [48]) has shown that when one moving object makes contact with another, and then the second, without any delay, begins to move, this interaction is perceived as causal with the first object causing the movement of the second. Michotte called this phenomenon the 'launching' effect.…”
Section: (D) Temporal Delaymentioning
confidence: 99%
“…Perhaps the most studied of these factors that affect judgements of causality is temporal contiguity. Michotte ([47], and see [48]) has shown that when one moving object makes contact with another, and then the second, without any delay, begins to move, this interaction is perceived as causal with the first object causing the movement of the second. Michotte called this phenomenon the 'launching' effect.…”
Section: (D) Temporal Delaymentioning
confidence: 99%
“…If displacement is not necessarily coupled with oculomotor overshoot more generally, oculomotor overshoot might mediate or modulate forward displacement with smooth motion targets, and a third variable (e.g., high-level expectation) would be the ultimate cause of displacement with smooth motion targets. Indeed, "displacement ϭ constant delay * velocity" does not account for important aspects of forward displacement with smooth motion targets (e.g., differences between launched and unlaunched targets [Hubbard, Blessum, & Ruppel, 2001], effects of verbal cue validity [Hubbard, 1994]) unless a third variable, such as high-level expectation, influences eye movements. Kerzel (2006) admits that "high-level factors such as expectations about the future trajectory of the target may influence smooth pursuit eye movements" (p. 167) and "smooth pursuit eye movements are always predictive in nature and prediction is a high-level process" (p. 168).…”
Section: Oculomotor Overshootmentioning
confidence: 99%
“…Sometimes when adult humans observe a moving object that disappears, they will misremember the location of its disappearance in way that reflects its momentum; this effect is called representational momentum (Freyd & Finke 1984;Hubbard 2010). e trajectories implied by representational momentum reveal that the effect reflects impetus mechanics rather than Newtonian principles (Freyd & Jones 1994;Kozhevnikov & Hegarty 2001;Hubbard et al 2001;Hubbard 2013). And these trajectories are independent of subjects' scientific knowledge (Freyd & Jones 1994;Kozhevnikov & Hegarty 2001).…”
mentioning
confidence: 99%